The Effectiveness of Using Card Games to Improve Vocabulary Acquisition - Sulistiyani (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2018)
Teaching vocabulary at elementary school is not easy. In many stages the students’ interest in learning English is usually spontaneous. Teaching vocabulary to elementary schools, the teacher should and can make the students relax and interested, so they will be happy to learn it. If they feel happy, they will arouse their inner motivation. The problems which will be investigated in this study are formulated as follows: (1) What are the features of vocabulary taught to the first grade students of elementary level? (2) Is there any significant difference between the acquisition of vocabulary by the students who are taught using card games and the students taught conventionally? The teachers use games as their teaching aid. The students really appreciate any kind of game activities which provide excitement and fun. It will be easy to understand and practice English. The researcher chooses games as the simple illustrated media to facilitate students’ method of learning, as children learn while playing games. It is easy to be understood and comprehended by students. The subjects of the study who are grouped into two classes, each of the classes contains 30 students who means that the subjects of the study are 60 students. They have the same ability of the knowledge. The writer uses standardized test, It consist of 25 items with the allocated time of 60 minutes for pre-test and post test. The writer involves two classes.The total number of the first grade students are 60, 30 students belong to A class and the other 30 students belong to B class. In this study, A class is choosen for the experimental group, and B class for the control group, the writer use T-test, The test is to find out students achievement in a process without using card games and the second test is used to find out the differences, the writer calculate the correlation among them by using T-test formula. To calculate the data, the researcher uses spss program. The data analysis above is description that t-test is 2.676 and degree of freedom ( df ) = (60-1-1)=58 at standard significant 0,05. So t-table is 2.002 from the data can take conclusion that t-test >. t-table (2.676 > 2.002) . Based on the result, Ho is refused because t-test > t-table means that there is influence or significant differences.